ANALISIS RESIDU KLORPIRIFOS DALAM SAYUR-SAYURAN DENGAN TEKNIK HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2016)
The research about analysis of chlorpyrifos residue in vegetables by using High Performance Liquid Chromatography (HPLC) technique has been done. To obtain the optimal measurement results, the measurement performed several important parameters in the chromatographic system was composition of mobile phase, volume injection sample, flow rate and pH eluent. Optimum measurement conditions obtained was mobile phase composition (water : methanol) with 70 : 30, volume injection sample are 5 mL, flow rate are 0.5mL/menit and pH eluent are 7. The analytical performance that obtained is good showed with the reproducibility value as percentage coefficient variance (% CV) was 0.0664%, limit of detection (LOD) was 0.44 ppm, with a recovery percentage of > 95%. The results obtained showed the HPLC technique can be used for the routine analysis in the determination of chlorpyrifos for the vegetable samples.